2021
DOI: 10.1186/s12889-021-11838-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparities in access to care for time-sensitive conditions during COVID-19 pandemic in Chile

Abstract: Background During the COVID-19 pandemic, reductions in healthcare utilization are reported in different contexts. Nevertheless, studies have not explored specifically gender disparities in access to healthcare in the context of COVID-19. Methods To evaluate gender disparities in access to medical in Chile we conducted an interrupted time series analysis using segmented regression. The outcome variable was the number of weekly confirmed cases of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
1
9
1
3
Order By: Relevance
“… 17 New stroke and myocardial infarction diagnoses decreased by 9,047 cases in men and 10,315 cases in women in Chile. 19 In Italy, the Lazio and Rome region saw almost a 70% decline in ST-segment elevation myocardial infarction admissions, and the Bologna region saw a 58% decline in CVD-related emergency department visits, with a 10% decline in CVD admissions. 20 , 21 In Austria, the Styria region saw the likelihood of an admission for MI decline by a quarter.…”
Section: Health Facility Admissions or Visitsmentioning
confidence: 99%
“… 17 New stroke and myocardial infarction diagnoses decreased by 9,047 cases in men and 10,315 cases in women in Chile. 19 In Italy, the Lazio and Rome region saw almost a 70% decline in ST-segment elevation myocardial infarction admissions, and the Bologna region saw a 58% decline in CVD-related emergency department visits, with a 10% decline in CVD admissions. 20 , 21 In Austria, the Styria region saw the likelihood of an admission for MI decline by a quarter.…”
Section: Health Facility Admissions or Visitsmentioning
confidence: 99%
“…De Rosa et al [ 3 ] in Italy found a higher reduction for females admitted with STEMI (41.2%; p = 0.011) than males (17.8%; p = 0.191). Further, Pacheco et al [ 19 ] documented a greater reduction in females compared to males of myocardial infarction admissions (level effect = 0.595 (0.566-0.627) versus 0.532 (0.502-0.564)).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been conducted to investigate the gender differences in patients hospitalized with ACS during the COVID-19 pandemic with divergent results regarding the admission frequency, invasive procedures, and outcomes [ 3 , 17 - 19 ]. Therefore, we undertook this study to investigate the gender differences in hospitalizations and in-hospital outcomes of patients with ACS during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that women are more likely to be diagnosed and receive care for non-communicable diseases due to a greater awareness of the signs and symptoms of these diseases and, consequently, an increase in seeking care in health centers [25]. However, barriers in access to health services have been accentuated with the pandemic, such as having less free time due to family responsibilities, a reduction in the ability to pay for health care due to shorter work hours, higher unemployment, decreased economic income, and the fear of being infected by COVID-19 [26]. In this way, the delay in the care of patients with chronic diseases may affect the probability of presenting CDR.…”
Section: Discussionmentioning
confidence: 99%